(3QSGdI aj MSf cJGHI GdbQBf hNdb EHdjS eSJdI ef cJGH JgPjH GdfaS aj eYQaI GdePGgH GdNeSs - (3GdMdj, CHh efUhQ, GHf GdeWgQ, LeGd GdOjf, GdMSf Hf jhSa Hf Ydj GHf GdeWgQ, J (B726(3g`s
(3ChdgG (B:s
(3bGd TjNfG (B... (3GdKGdK ef cJGHI GdbQGf hLH HfPQ hTHgI adG jLhR ddMOK eS cJGHI GdbQBf hHg bGd GdabgGA hdG jMQe eS CWQGa GdChQGb GdNGdjI Yf GdcJGHI hgGeTg hGdeUMa HZdGag (B...s
(3BNQgG (B:s
(3bGd CYQGHj dYdj Ydjg GdSdGe (B: (3je fdJ eG fdJ ? bGd (B: (3jG GYQGHj bYOJ Ydi HGH bdHj ade COY Cf jONdg TjA Shi Gddg (B. (3UOb hdj Gddg (B... (3JeJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B2\227s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3GdJaSjQ hYdhe GdbQBfs